Debt Literacy, Financial Management Practice, Financial Confidence pada Over-indebtedness Guru: Studi pada Guru di Kabupaten Karawang - Habieb Prasojo, Luqman; Dewi Tanzil, Nanny; Adrianto, Zaldy; Wahyuni, Ersa Tri (Universitas Pasundan, 2024)
The unstoppable growth of fintech, accelerated by the pandemic, is reflected in the increasing financial inclusion and literacy rates in Indonesia, as observed by the OJK. P2P Lending has become one of the most popular fintech services, offering accessible and affordable loans to various segments of society. However, the ease of access has led to challenges, with many individuals, including teachers, facing the risks of over-indebtedness. This study investigates the role of debt literacy, financial management practices, and financial confidence in influencing over-indebtedness among teachers in Karawang Regency. Using a quantitative approach, data from 385 teachers were analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the complex relationships between variables, considering the influence of demographic factors. The findings reveal that debt literacy and financial management practices have no significant negative impact on over-indebtedness, while financial confidence has no significant positive impact.